The application of motivation model to the integrated economic and social system (Путеводитель предпринимателя)
This article analyzes the problem of creating an integrated management system with the application of motivation model. Such system has three levels or subsystems which are considered to be the best suited for the integrated economic and social system being created, because the development of controlling mechanism and criteria of such system requires to identify the significance of different levels.